1% for 10%: Executive Strategies for Customer Care - Kakabadse, Andrew P.; Savery, Lawson; Kakabadse, Nada K.; Lee-Davies, Linda (John Wiley & Sons, Ltd, 2006)
This paper avoids the linear route to establishing where the biggest impact on customer service lies and instead examines the influences on the quality of the customer experience from all angles in an organization. From the culture and policies of the organization itself, to the front-line individuals and their managers, it is evident that customer satisfaction is influenced at many levels and this directly affects organizational success and competitive standing. The Cranfield Top Executive Leadership studies, across 12 countries, examine senior managers' commitment to customer focus. The sample's division, into three distinct groups according to their customer focus commitment levels, highlights a range of arguments about individual, management and corporate dedication to levels of customer satisfaction with hints at where these may conflict with each other. By taking a rounded look at the customer focus process from all its pivots within an organization, potential bottlenecks in the process are also highlighted. Most interestingly, it is concluded that there is actually little difference between the groups in pure quantitative terms, but it is that small difference indeed which makes all the difference to a substantial increase in positive customer experience.